Magnetic resonance imaging of Ménière's disease: early clinical experience in a UK centre. Issue 4 (3rd April 2020) - Pai, I; Mendis, S; Murdin, L; Touska, P; Connor, S
Abstract: Background: Recent developments in magnetic resonance imaging have enabled demonstration of endolymphatic hydrops, and the clinical application of these imaging studies in Ménière's disease is being explored. Objective: To evaluate our centre's experience to date of hydrops magnetic resonance imaging in patients with episodic vertigo. Methods: Magnetic resonance imaging was performed using a high-resolution three-dimensional fluid-attenuated inversion recovery sequence on a 3 Tesla scanner at 4 hours following double-dose gadolinium administration. Results: The study included 31 patients, 28 of whom had a clinical diagnosis of Ménière's disease. In unilateral Ménière's disease, magnetic resonance imaging was able to lateralise endolymphatic hydrops to the clinically symptomatic ear in all cases. Mild hydrops was often seen in clinically asymptomatic ears. Conclusion: There is a good correlation between the clinical symptoms and lateralisation of hydropic changes on magnetic resonance imaging. Further refinements of imaging techniques and grading system will likely improve the diagnostic accuracy and clinical utilisation of hydrops magnetic resonance imaging.